Exploring Determinants of `Mental Distance' in Cross-Border Contexts - Henrik Basche (Tijdschrift voor economische en sociale geografie, 2021)
State-of-the-art research has identified mental distance, which is the limited perception of occurrences beyond one's country's border, as the main determinant of moderate cross-border interactions in Europe. While it is well understood that mental distance is an upstream process that occurs prior to (bounded) rational decision-making, it is not clear whether and, if so, which determinants affect the degree of mental distance. Standardised interviews with inhabitants of the Euregio Meuse–Rhine cross-border region were conducted in 2019 to detect the potential effects of language (areas), sociodemographic characteristics and centre–periphery relations. The results demonstrate that knowledge of regionally spoken languages (German, French and Dutch) leads to a lower mental distance in four out of five cases, whereas English abilities surprisingly have the opposite effect. In addition, the outcomes indicate that centre–periphery relations can outweigh the fact that two cross-border sub-regions share the same official language.
Keywords: 330; Mental distance; Euregio Meuse–Rhine; cross-border interactions; knowledge of foreign languages; centre-periphery relations; inferential statistics